Incorporating operational flexibility into mine waste management - Narendranathan, S; Johns, C; Ralls, G (Mine Waste 2010: Proceedings of the First International Seminar on the Reduction of Risk in the Management of Tailings and Mine Waste, 2010)
A case study is presented that describes the benefits of optimised slope monitoring of an in-pit tailings storage facility embankment. As the tailings storage design project quickly advanced from concept to construction, the original tailings facility design criteria and embankment performance requirements were progressively modified to meet mine operational requirements. An embankment slope monitoring program was developed to facilitate safe tailings disposal in close proximity to mining operations.